Legal Constructions of Apprenticeship for Notary Candidates in the Framework of Rechtsidee - Yetniwati Yetniwati; Taufik Yahya; Pahlefi Pahlefi (Faculty of Law, Jambi University, 2021)
This article discusses the concept of the legal construction of notary candidate apprenticeship within the framework of rechtsidee (law ideals). This article demonstrates that the so called rechtidee has always focused on three ideals, namely legal certainty, legal justice, and legal benefit. With regards to apprenticeship, it is argued, however, that these three ideals are not sufficient. Most legal studies have forgotten another basic ideal, namely the education principal which is inevitable in establishing a professional and qualified notary. The article demonstrates how the apprenticeship should be addressed to reveal the concept of legal construction for prospective public notaries. It is believed that there is a legal but moral relationship between a notary candidate and a notary public apprentice under the supervision of the government or a designated official. The principles of education in apprenticeships would enable the notary candidates to have sufficient knowledge and wisdom, and other character buildings like dedication, harmony, mutual relationships, role model, as well as, but not limited to, honesty. Given its functions, apprenticeship legal construction has to be developed in regulations not only based on the principles of legal certainty, legal justice, and legal benefit, but also on the principles of education